Solid electrolyte material and battery using the same
By optimizing the composition and structure of Li, M, O and X in solid electrolyte materials, ensuring their X-ray diffraction characteristics, solving the problem of decreasing ion conductivity at high temperatures, and achieving efficient heat resistance and safety of lithium-ion batteries .
Patent Information
- Application Number
- CN202180070475.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-30
- Filing Date
- 2021-08-30
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2041-08-30
AI Technical Summary
Existing solid electrolyte materials tend to decrease ion conductivity at high temperatures, making it difficult to maintain stable performance in a temperature-changing environment.
Using solid electrolyte materials containing Li, M, O and X, Cu-Kα ray X-ray diffraction measurement, ensure that the X-ray diffraction pattern has a specific diffraction angle range and intensity ratio, and form high lithium ion conductivity and excellent resistance. Thermal properties.
The ion conductivity is maintained at high temperatures, ensuring that the battery has stable charge and discharge characteristics in a temperature-changing environment, and reducing the safety risks caused by sulfur content.
Smart Images

Figure CN116529205B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a solid electrolyte material and a battery using the same. Background Art
[0002] Patent Documents 1 and 2 disclose solid electrolyte materials containing Li, M, O, and X. Here, M is at least one element selected from Nb and Ta, and X is at least one element selected from Cl, Br, and I.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: International Publication No. 2020 / 137153
[0006] Patent Document 2: International Publication No. 2020 / 137155 Summary of the invention
[0007] Problems to be solved by the invention
[0008] An object of the present disclosure is to provide a solid electrolyte material having practical ion conductivity and capable of reducing a decrease in ion conductivity caused by heat.
[0009] Means for solving problems
[0010] The present disclosure relates to a solid electrolyte material, which is a solid electrolyte material containing Li, M, O and X, wherein:
[0011] M is at least one selected from Nb and Ta,
[0012] X is at least one selected from F, Cl, Br and I,
[0013] The solid electrolyte material has a first peak located within a range of a diffraction angle 2θ of 13.49° to 13.59° and a second peak located within a range of a diffraction angle 2θ of 14.82° to 14.92° in an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα rays,
[0014] The intensity ratio of the first peak to the second peak is 0.50 or more and 4.50 or less.
[0015] Effects of the Invention
[0016] The present disclosure provides a solid electrolyte material having practical ion conductivity and capable of reducing a decrease in ion conductivity caused by heat. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1A cross-sectional view showing a battery 1000 according to a second embodiment.
[0018] Figure 2 A cross-sectional view showing an electrode material 1100 according to the second embodiment.
[0019] Figure 3 A schematic diagram showing a press mold 300 for evaluating the ion conductivity of a solid electrolyte material.
[0020] Figure 4 It is a graph showing the X-ray diffraction patterns of the solid electrolyte materials of Examples 1 to 3 and Comparative Examples 1 and 2. DETAILED DESCRIPTION
[0021] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. The present disclosure is not limited to the following embodiments.
[0022] (First embodiment)
[0023] The solid electrolyte material of the first embodiment contains Li, M, O and X. M is at least one selected from Nb and Ta. X is at least one selected from F, Cl, Br and I. The solid electrolyte material of the first embodiment has a first peak located in the range of diffraction angle 2θ of 13.49° to 13.59° and a second peak located in the range of diffraction angle 2θ of 14.82° to 14.92° in the X-ray diffraction spectrum obtained by X-ray diffraction measurement using Cu-Kα rays. The intensity ratio of the first peak to the second peak is 0.50 to 4.50. Furthermore, when there are multiple peaks in the range of diffraction angle 2θ of 13.49° to 13.59°, the first peak is the peak with the maximum intensity among these multiple peaks. Furthermore, when a plurality of peaks exist within the range of the diffraction angle 2θ of 14.82° to 14.92°, the second peak is a peak having the maximum intensity among the plurality of peaks.
[0024] The solid electrolyte material containing Li, M, O, and X of the first embodiment contains a crystalline phase having the above-mentioned X-ray diffraction pattern. By containing this crystalline phase, the solid electrolyte material of the first embodiment has practical ion conductivity and can reduce the decrease in ion conductivity caused by heat.
[0025] In more detail, in the solid electrolyte material containing the crystalline phase having the above X-ray diffraction pattern and containing Li, M, O and X, while easily forming a path for lithium ion diffusion, the evaporation of the constituent elements caused by heat can also be suppressed. As a result, the solid electrolyte material of the first embodiment can reduce the decrease in ion conductivity caused by heat while achieving practical ion conductivity. The solid electrolyte material of the first embodiment can have, for example, high lithium ion conductivity and excellent heat resistance.
[0026] Here, an example of a high lithium ion conductivity is, for example, 4.0 mS / cm or more at around room temperature. The solid electrolyte material of the first embodiment can have an ion conductivity of, for example, 4.0 mS / cm or more.
[0027] Next, an example of the heat to which the solid electrolyte material is exposed is described. When manufacturing a large battery, a heat treatment process at high temperature is required for densification and bonding in the positive electrode, electrolyte layer and negative electrode of the battery. The temperature in the heat treatment process is, for example, about 200°C. Even when a heat treatment of about 200°C is implemented, the decrease in the ion conductivity of the solid electrolyte material of the first embodiment can be reduced or the ion conductivity can not be reduced. In this way, the solid electrolyte material of the first embodiment has excellent heat resistance. Therefore, the solid electrolyte material of the first embodiment can be used to obtain a battery with excellent charge and discharge characteristics.
[0028] The solid electrolyte material of the first embodiment can maintain high lithium ion conductivity within the assumed battery use temperature range (eg, -30°C to 80°C). Therefore, a battery using the solid electrolyte material of the first embodiment can operate stably even in an environment with temperature changes.
[0029] The solid electrolyte material of the first embodiment can be used to obtain a battery having excellent charge and discharge characteristics. An example of the battery is an all-solid battery. The all-solid battery may be a primary battery or a secondary battery.
[0030] From the viewpoint of safety, the solid electrolyte material of the first embodiment is preferably substantially free of sulfur. The so-called substantially free of sulfur in the solid electrolyte material of the first embodiment means that the solid electrolyte material does not contain sulfur as a constituent element except for sulfur inevitably mixed in as an impurity. In this case, the sulfur mixed in the solid electrolyte material as an impurity is, for example, 1 mol% or less. From the viewpoint of safety, the solid electrolyte material of the first embodiment is preferably free of sulfur. The solid electrolyte material that does not contain sulfur will not generate hydrogen sulfide even if exposed to the atmosphere, so it is excellent in safety.
[0031] In order to improve the ion conductivity and heat resistance of the solid electrolyte material, the solid electrolyte material of the first embodiment may be substantially composed of Li, M, O and X. Here, "the solid electrolyte material of the first embodiment is substantially composed of Li, M, O and X" means that the total amount of Li, M, O and X is 90% or more relative to the total amount of all elements constituting the solid electrolyte material of the first embodiment. As an example, the ratio may be 95% or more.
[0032] The solid electrolyte material of the first embodiment may be composed of Li, M, O, and X only in order to improve the ion conductivity and heat resistance of the solid electrolyte material.
[0033] In order to improve the ion conductivity and heat resistance of the solid electrolyte material, in the solid electrolyte material of the first embodiment, X may contain Cl. X may also be Cl.
[0034] In order to improve the ion conductivity and heat resistance of the solid electrolyte material, in the solid electrolyte material of the first embodiment, M may contain Ta. M may be Ta.
[0035] In order to improve the ion conductivity and heat resistance of the solid electrolyte material, in the solid electrolyte material of the first embodiment, the molar ratio of Li to M may be 1.2 or more and 1.4 or less.
[0036] The X-ray diffraction spectrum of the solid electrolyte material of the first embodiment can be obtained using Cu-Kα rays (wavelength and That is, wavelengths of 0.15405 nm and 0.15444 nm), and are obtained by X-ray diffraction measurement based on the θ-2θ method.
[0037] The diffraction angle of a peak in an X-ray diffraction pattern can be defined as the angle of maximum intensity of a mountain-shaped portion when the SN ratio (i.e., the ratio of signal S to background noise N) is greater than 3 and the half-width is less than 10°. The half-width refers to the maximum intensity of the X-ray diffraction peak when the maximum intensity is 1 MAX When the intensity is I MAX The width is represented by half the value of the difference between the two diffraction angles.
[0038] As described above, in the X-ray diffraction spectrum of the solid electrolyte material of the first embodiment, the intensity ratio of the first peak to the second peak is 0.50 to 4.50. The intensity ratio of the first peak to the second peak may be 0.70 to 1.72 or 1.05 to 1.72.
[0039] The upper limit and lower limit of the intensity ratio of the first peak to the second peak can be defined by any combination selected from numerical values of 0.50, 0.7, 1.0, 1.05, 1.5, 1.72, 2.0, 2.5, 3.0, 3.5, 4.0, and 4.50.
[0040] The shape of the solid electrolyte material of the first embodiment is not limited. Examples of the shape are needle-shaped, spherical, or ellipsoidal. The solid electrolyte material of the first embodiment may also be particles. The solid electrolyte material of the first embodiment may also be formed in a pellet or plate shape.
[0041] When the shape of the solid electrolyte material of the first embodiment is a particle (e.g., spherical), the solid electrolyte material may have a median particle size of 0.1 μm or more and 100 μm or less, or may have a median particle size of 0.5 μm or more and 10 μm or less. Thus, the solid electrolyte material of the first embodiment and other materials can be well dispersed. The median particle size of the particle means the particle size (d50) equivalent to 50% of the volume accumulation in the volume-based particle size distribution. The volume-based particle size distribution can be measured by a laser diffraction measuring device or an image analysis device.
[0042] When the solid electrolyte material of the first embodiment is in the form of particles (eg, spheres), the solid electrolyte material may have a smaller median diameter than the active material. Thus, the solid electrolyte material of the first embodiment and the active material can be in a well-dispersed state.
[0043] <Method for producing solid electrolyte material>
[0044] The solid electrolyte material of the first embodiment can be produced by the following method.
[0045] The raw material powder is prepared so as to have a target composition. Examples of the raw material powder are oxides, hydroxides, halides or acid halides.
[0046] As an example, in a solid electrolyte material composed of Li, Ta, O and Cl (that is, a solid electrolyte material in which M is Ta and X is Cl), when the molar ratio Li / M when the raw materials are mixed is 1.3, Li2O2 and TaCl5 are mixed at a molar ratio of Li2O2:TaCl5=0.65:1.0. M and X are determined by selecting the raw material powder. The molar ratio of Li / M is determined by selecting the mixing ratio of the raw material powder. The raw material powders may also be mixed at a pre-adjusted molar ratio in a manner to offset composition changes that may occur during the synthesis process.
[0047] The reactant can be obtained by calcining the mixture of raw material powders. In order to suppress the evaporation of the raw materials caused by calcination, the mixture of raw material powders can also be sealed in an airtight container formed by quartz glass or borosilicate glass and calcined under vacuum or inert gas atmosphere. The inert gas atmosphere is, for example, an argon atmosphere or a nitrogen atmosphere. Alternatively, the reactant can be obtained by causing the mixture of raw material powders to react with each other in a mechanochemical manner in a mixing device such as a planetary ball mill. In other words, the raw materials can also be mixed and reacted using a mechanochemical grinding method. The solid electrolyte material of the first embodiment can be obtained by these methods.
[0048] By firing the solid electrolyte material, a part of M or a part of X may evaporate. As a result, the molar ratio Li / M of the obtained solid electrolyte material may be larger than the value calculated from the molar ratio of the prepared raw material powder.
[0049] The position of the X-ray diffraction peak in the solid electrolyte material of the first embodiment, that is, the structure of the crystal phase can be adjusted to a desired structure by selecting the type of raw material powder, the mixing ratio of the raw material powder, and the reaction conditions.
[0050] The composition of the solid electrolyte material can be determined, for example, by inductively coupled plasma (ICP) emission spectrometry, ion chromatography, or inert gas fusion-infrared absorption. For example, the composition of Li and M can be determined by ICP emission spectrometry, the composition of X can be determined by ion chromatography, and O can be determined by inert gas fusion-infrared absorption.
[0051] (Second embodiment)
[0052] The second embodiment will be described below. Matters described in the first embodiment may be omitted as appropriate.
[0053] The battery of the second embodiment comprises a positive electrode, an electrolyte layer and a negative electrode. The electrolyte layer is arranged between the positive electrode and the negative electrode. At least one selected from the positive electrode, the electrolyte layer and the negative electrode contains the solid electrolyte material of the first embodiment.
[0054] The battery of the second embodiment contains the solid electrolyte material of the first embodiment. Therefore, even when the battery is exposed to high temperature for heat treatment at high temperature during battery production, the battery of the second embodiment has excellent charge and discharge characteristics.
[0055] Figure 1 A cross-sectional view showing a battery 1000 according to a second embodiment.
[0056] The battery 1000 includes a positive electrode 201 , an electrolyte layer 202 , and a negative electrode 203 . The electrolyte layer 202 is disposed between the positive electrode 201 and the negative electrode 203 .
[0057] The positive electrode 201 includes positive electrode active material particles 204 and solid electrolyte particles 100 .
[0058] The electrolyte layer 202 contains an electrolyte material. The electrolyte material is, for example, a solid electrolyte material.
[0059] The negative electrode 203 includes negative electrode active material particles 205 and solid electrolyte particles 100 .
[0060] The solid electrolyte particle 100 is a particle containing the solid electrolyte material of the first embodiment. The solid electrolyte particle 100 may also be a particle containing the solid electrolyte material of the first embodiment as a main component. The so-called particle containing the solid electrolyte material of the first embodiment as a main component means a particle containing the solid electrolyte material of the first embodiment as the largest component in molar ratio. The solid electrolyte particle 100 may also be a particle composed of the solid electrolyte material of the first embodiment.
[0061] The positive electrode 201 contains a material that can absorb and release metal ions such as lithium ions. The positive electrode 201 contains, for example, a positive electrode active material (for example, positive electrode active material particles 204).
[0062] Examples of positive electrode active materials are lithium-containing transition metal oxides, transition metal fluorides, polyanionic materials, fluorinated polyanionic materials, transition metal sulfides, transition metal oxysulfides or transition metal oxynitrides. Examples of lithium-containing transition metal oxides are Li(Ni, Co, Al)O2, Li(Ni, Co, Mn)O2 or LiCoO2.
[0063] In the present disclosure, “(A, B, C)” means “at least one selected from A, B, and C”.
[0064] From the viewpoint of battery cost and safety, lithium phosphate may be used as the positive electrode active material.
[0065] When the positive electrode 201 contains the solid electrolyte material of the first embodiment and X contains I (i.e., iodine), lithium iron phosphate can also be used as the positive electrode active material. The solid electrolyte material of the first embodiment containing I is easily oxidized. If lithium iron phosphate is used as the positive electrode active material, the oxidation reaction of the solid electrolyte material can be suppressed. In other words, the formation of an oxide layer with low lithium ion conductivity can be suppressed. As a result, the battery has a higher charge and discharge efficiency.
[0066] The positive electrode 201 contains not only the solid electrolyte material of the first embodiment, but also a transition metal fluoride oxide as a positive electrode active material. Even if the solid electrolyte material of the first embodiment is fluorinated by a transition metal fluoride, it is difficult to form a resistance layer. As a result, the battery has a high charge and discharge efficiency.
[0067] Transition metal fluoride oxide contains oxygen and fluorine. As an example, the transition metal fluoride oxide can also be a composition formula Li p Me q O m F n Here, Me is at least one selected from Mn, Co, Ni, Fe, Al, Cu, V, Nb, Mo, Ti, Cr, Zr, Zn, Na, K, Ca, Mg, Pt, Au, Ag, Ru, W, B, Si and P, and satisfies the mathematical formula: 0.5≤p≤1.5, 0.5≤q≤1.0, 1≤m<2 and 0<n≤1. Examples of such transition metal fluoride oxides are Li 1.05 (Ni 0.35 Co 0.35 Mn 0.3 ) 0.95 O 1.9 F 0.1 .
[0068] The positive electrode active material particles 204 may also have a median particle size of 0.1 μm or more and 100 μm or less. When the positive electrode active material particles 204 have a median particle size of 0.1 μm or more, the positive electrode active material particles 204 and the solid electrolyte particles 100 can form a good dispersion state in the positive electrode 201. As a result, the charge and discharge characteristics of the battery are improved. When the positive electrode active material particles 204 have a median particle size of 100 μm or less, the lithium diffusion rate in the positive electrode active material particles 204 can be increased. As a result, the battery can operate at a high output power.
[0069] The positive electrode active material particles 204 may have a larger median diameter than the solid electrolyte particles 100. This allows the positive electrode active material particles 204 and the solid electrolyte particles 100 to be in a well-dispersed state.
[0070] From the viewpoint of battery energy density and output, in the positive electrode 201 , the ratio of the volume of the positive electrode active material particles 204 to the total volume of the positive electrode active material particles 204 and the volume of the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.
[0071] Figure 2A cross-sectional view showing an electrode material 1100 according to a second embodiment. The electrode material 1100 is contained in, for example, a positive electrode 201. In order to prevent the solid electrolyte particles 100 from reacting with the positive electrode active material (i.e., the electrode active material particles 206), a coating layer 216 may be formed on the surface of the electrode active material particles 206. Thus, the increase in the reaction overpotential of the battery can be suppressed. Examples of the coating material contained in the coating layer 216 are a sulfide solid electrolyte, an oxide solid electrolyte, or a halide solid electrolyte.
[0072] When the solid electrolyte particle 100 is a sulfide solid electrolyte, the coating material may be the solid electrolyte material of the first embodiment, and X may be at least one selected from Cl and Br. Such a solid electrolyte material of the first embodiment is difficult to oxidize compared to a sulfide solid electrolyte. As a result, the increase in the reaction overpotential of the battery can be suppressed.
[0073] When the solid electrolyte particle 100 is the solid electrolyte material of the first embodiment and X contains I, the coating material may be the solid electrolyte material of the first embodiment and X may be at least one selected from Cl and Br. The solid electrolyte material of the first embodiment not containing I is difficult to oxidize compared to the solid electrolyte material of the first embodiment containing I. As a result, the battery has a higher charge and discharge efficiency.
[0074] When the solid electrolyte particle 100 is the solid electrolyte material of the first embodiment and X contains I, the coating material may also contain an oxide solid electrolyte. The oxide solid electrolyte may also be lithium niobate which has excellent stability even at high potential. Thus, the battery has a high charge and discharge efficiency.
[0075] The positive electrode 201 may also be composed of a first positive electrode layer containing a first positive electrode active material and a second positive electrode layer containing a second positive electrode active material. Here, the second positive electrode layer is disposed between the first positive electrode layer and the electrolyte layer 202, and the first positive electrode layer and the second positive electrode layer contain a solid electrolyte material of the first embodiment containing I and form a coating layer 216 on the surface of the second positive electrode active material. According to the above configuration, the solid electrolyte material of the first embodiment contained in the electrolyte layer 202 can be inhibited from being oxidized by the second positive electrode active material. As a result, the battery has a higher charging capacity. Examples of coating materials contained in the coating layer 206 are sulfide solid electrolytes, oxide solid electrolytes, polymer solid electrolytes, or halide solid electrolytes. However, when the coating material is a halide solid electrolyte, I is not contained as a halogen element. The first positive electrode active material may be the same material as the second positive electrode active material, or may be a material different from the second positive electrode active material.
[0076] From the viewpoint of the energy density and output of the battery, the positive electrode 201 may have a thickness of 10 μm or more and 500 μm or less.
[0077] The electrolyte layer 202 contains an electrolyte material. The electrolyte material is, for example, a solid electrolyte material. The electrolyte layer 202 may also be a solid electrolyte layer. The electrolyte layer 202 may also contain the solid electrolyte material of the first embodiment. The electrolyte layer 202 may also be composed only of the solid electrolyte material of the first embodiment.
[0078] The electrolyte layer 202 may also be composed only of a solid electrolyte material different from the solid electrolyte material of the first embodiment. Examples of solid electrolyte materials different from the solid electrolyte material of the first embodiment are Li2MgX'4, Li2FeX'4, Li(Al, Ga, In)X'4, Li3(Al, Ga, In)X'6, or LiI. Here, X' is at least one selected from F, Cl, Br, and I.
[0079] Hereinafter, the solid electrolyte material of the first embodiment is referred to as a first solid electrolyte material. A solid electrolyte material different from the solid electrolyte material of the first embodiment is referred to as a second solid electrolyte material.
[0080] The electrolyte layer 202 may contain not only the first solid electrolyte material but also the second solid electrolyte material. The first solid electrolyte material and the second solid electrolyte material may be uniformly dispersed. The layer composed of the first solid electrolyte material and the layer composed of the second solid electrolyte material may also be stacked along the stacking direction of the battery 1000.
[0081] The electrolyte layer 202 may have a thickness of 1 μm or more and 100 μm or less. When the electrolyte layer 202 has a thickness of 1 μm or more, the positive electrode 201 and the negative electrode 203 are less likely to short-circuit. When the electrolyte layer 202 has a thickness of 100 μm or less, the battery can operate at a high output power.
[0082] Another electrolyte layer may be further provided between the electrolyte layer 202 and the negative electrode 203. That is, a second electrolyte layer may be further provided between the electrolyte layer 202 and the negative electrode 203. For example, when the electrolyte layer 202 contains a first solid electrolyte material, in order to more stably maintain the higher ion conductivity of the first solid electrolyte material, an electrolyte layer composed of another solid electrolyte material that is electrochemically stable compared to the first solid electrolyte material may be further provided between the electrolyte layer 202 and the negative electrode 203.
[0083] The negative electrode 203 contains a material that can insert and remove metal ions (eg, lithium ions). The negative electrode 203 contains, for example, a negative electrode active material (eg, negative electrode active material particles 205).
[0084] Examples of negative electrode active materials are metal materials, carbon materials, oxides, nitrides, tin compounds or silicon compounds. The metal material may be a single metal or an alloy. Examples of metal materials are lithium metal or lithium alloys. Examples of carbon materials are natural graphite, coke, graphitizable carbon, carbon fiber, spherical carbon, artificial graphite or amorphous carbon. From the viewpoint of capacity density, suitable examples of negative electrode active materials are silicon (i.e. Si), tin (i.e. Sn), silicon compounds or tin compounds.
[0085] The negative electrode active material can also be selected based on the reduction resistance of the solid electrolyte material contained in the negative electrode 203. When the negative electrode 203 contains the first solid electrolyte material, a material that can embed and deintercalate lithium ions at 0.27V or more relative to lithium can also be used as the negative electrode active material. If the negative electrode active material is such a material, the reduction of the first solid electrolyte material contained in the negative electrode 203 can be suppressed. As a result, the battery has a higher charge and discharge efficiency. Examples of this material are titanium oxide, indium metal or lithium alloy. An example of titanium oxide is Li4Ti5O 12 , LiTi2O4 or TiO2.
[0086] The negative electrode active material particles 205 may also have a median particle size of 0.1 μm or more and 100 μm or less. When the negative electrode active material particles 205 have a median particle size of 0.1 μm or more, the negative electrode active material particles 205 and the solid electrolyte particles 100 can form a good dispersion state in the negative electrode 203. As a result, the charge and discharge characteristics of the battery are improved. When the negative electrode active material particles 205 have a median particle size of 100 μm or less, the lithium diffusion rate in the negative electrode active material particles 205 can be increased. As a result, the battery can operate at a high output power.
[0087] The negative electrode active material particles 205 may have a larger median diameter than the solid electrolyte particles 100. This allows the negative electrode active material particles 205 and the solid electrolyte particles 100 to be in a well-dispersed state.
[0088] From the viewpoint of battery energy density and output, in the negative electrode 203 , the ratio of the volume of the negative electrode active material particles 205 to the total volume of the negative electrode active material particles 205 and the volume of the solid electrolyte particles 100 may be 0.30 or more and 0.95 or less.
[0089] Figure 2The electrode material 1100 shown may also be contained in the negative electrode 203. In order to prevent the solid electrolyte particles 100 from reacting with the negative electrode active material (i.e., the electrode active material particles 206), a coating layer 216 may also be formed on the surface of the electrode active material particles 206. As a result, the battery has a higher charge and discharge efficiency. Examples of the coating material contained in the coating layer 216 are sulfide solid electrolytes, oxide solid electrolytes, polymer solid electrolytes, or halide solid electrolytes.
[0090] When the solid electrolyte particle 100 is the first solid electrolyte material, the coating material may also be a sulfide solid electrolyte, an oxide solid electrolyte, or a polymer solid electrolyte. An example of a sulfide solid electrolyte is Li2S-P2S5. An example of an oxide solid electrolyte is trilithium phosphate. An example of a polymer solid electrolyte is a composite compound of polyethylene oxide and a lithium salt. An example of such a polymer solid electrolyte is lithium bistrifluoromethanesulfonyl imide.
[0091] From the viewpoint of the energy density and output of the battery, the negative electrode 203 may have a thickness of 10 μm or more and 500 μm or less.
[0092] At least one selected from the positive electrode 201, the electrolyte layer 202, and the negative electrode 203 may also contain a second solid electrolyte material for the purpose of improving ion conductivity. Examples of the second solid electrolyte material are sulfide solid electrolytes, oxide solid electrolytes, halide solid electrolytes, or organic polymer solid electrolytes.
[0093] In the present disclosure, "sulfide solid electrolyte" means a solid electrolyte containing sulfur. "Oxide solid electrolyte" means a solid electrolyte containing oxygen. The oxide solid electrolyte may also contain anions other than oxygen (but excluding sulfur anions and halogen anions). "Halide solid electrolyte" means a solid electrolyte containing halogen elements and no sulfur. The halide solid electrolyte contains not only halogen elements but also oxygen.
[0094] Examples of sulfide solid electrolytes are Li2S-P2S5, Li2S-SiS2, Li2S-B2S3, Li2S-GeS2, Li 3.25 Ge 0.25 P 0.75 S4 or Li 10 GeP2S 12 .
[0095] Examples of oxide solid electrolytes include (i) NASICON-type solid electrolytes such as LiTi2(PO4)3 or its element substitution products, (ii) perovskite-type solid electrolytes such as (LaLi)TiO3, (iii) Li 14 ZnGe4O16 , LISICON type solid electrolytes such as Li4SiO4, LiGeO4 or their element substitution products, (iv) Li7La3Zr2O 12 Or a garnet-type solid electrolyte such as an element-substituted body thereof, or (v) Li3PO4 or its N-substituted body.
[0096] An example of a halide solid electrolyte is Li a Me' b Y c A compound represented by Z6. Here, the mathematical formulas a+mb+3c=6 and c>0 are satisfied. Me' is at least one selected from metal elements and semi-metal elements other than Li and Y. Z is at least one selected from F, Cl, Br and I. The value of m represents the valence of Me'.
[0097] "Semi-metallic elements" are B, Si, Ge, As, Sb and Te. "Metallic elements" are all elements contained in Groups 1 to 12 of the periodic table (but excluding hydrogen) and all elements contained in Groups 13 to 16 of the periodic table (but excluding B, Si, Ge, As, Sb, Te, C, N, P, O, S and Se).
[0098] In order to improve the ion conductivity of the halide solid electrolyte, Me' may be at least one selected from Mg, Ca, Sr, Ba, Zn, Sc, Al, Ga, Bi, Zr, Hf, Ti, Sn, Ta and Nb.
[0099] Examples of halide solid electrolytes are Li3YCl6 or Li3YBr6.
[0100] When the electrolyte layer 202 contains the first solid electrolyte material, the negative electrode 203 may also contain a sulfide solid electrolyte. Thus, the sulfide solid electrolyte, which is electrochemically stable with respect to the negative electrode active material, can inhibit the first solid electrolyte material and the negative electrode active material from contacting each other. As a result, the battery has a lower internal resistance.
[0101] Examples of organic polymer solid electrolytes include compounds of polymer compounds and lithium salts. The polymer compounds may also have an ethylene oxide structure. The polymer compounds having an ethylene oxide structure can contain a large amount of lithium salts and thus have higher ion conductivity.
[0102] Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9) or LiC(SO2CF3)3. One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used.
[0103] At least one selected from the positive electrode 201 , the electrolyte layer 202 , and the negative electrode 203 may contain a non-aqueous electrolyte solution, a gel electrolyte, or an ionic liquid for the purpose of facilitating the transfer of lithium ions and improving the output characteristics of the battery.
[0104] The non-aqueous electrolyte contains a non-aqueous solvent and a lithium salt dissolved in the non-aqueous solvent. Examples of non-aqueous solvents are cyclic carbonate solvents, chain carbonate solvents, cyclic ether solvents, chain ether solvents, cyclic ester solvents, chain ester solvents or fluorine solvents. Examples of cyclic carbonate solvents are ethylene carbonate, propylene carbonate or butylene carbonate. Examples of chain carbonate solvents are dimethyl carbonate, ethyl methyl carbonate or diethyl carbonate. Examples of cyclic ether solvents are tetrahydrofuran, 1,4-dioxane or 1,3-dioxolane. Examples of chain ether solvents are 1,2-dimethoxyethane or 1,2-diethoxyethane. Examples of cyclic ester solvents are γ-butyrolactone. Examples of chain ester solvents are methyl acetate. Examples of fluorine solvents are fluoroethylene carbonate, methyl fluoropropionate, fluorobenzene, ethyl fluoromethyl carbonate or dimethylene fluorocarbonate. One non-aqueous solvent selected therefrom may be used alone. Alternatively, a mixture of two or more non-aqueous solvents selected therefrom may be used.
[0105] Examples of lithium salts include LiPF6, LiBF4, LiSbF6, LiAsF6, LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9) or LiC(SO2CF3)3. One lithium salt selected from these may be used alone. Alternatively, a mixture of two or more lithium salts selected from these may be used. The concentration of the lithium salt is, for example, in the range of 0.5 mol / liter or more and 2 mol / liter or less.
[0106] As the gel electrolyte, a polymer material impregnated with a non-aqueous electrolyte can be used. Examples of the polymer material are polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate, or a polymer having an ethylene oxide bond.
[0107] Examples of cations contained in ionic liquids are:
[0108] (i) aliphatic chain quaternary salts such as tetraalkylammonium or tetraalkylphosphonium,
[0109] (ii) an aliphatic cyclic ammonium such as pyrrolidinium, morpholinium, imidazolinium, tetrahydropyrimidinium, piperazinium or piperidinium, or
[0110] (iii) Nitrogen-containing heterocyclic aromatic cations such as pyridinium and imidazolium cations.
[0111] An example of an anion contained in an ionic liquid is PF6 - 、BF4 - 、SbF6 - 、AsF6 - 、SO3CF3 - 、N(SO2CF3)2 - 、N(SO2C2F5)2 - 、N(SO2CF3)(SO2C4F9) - or C(SO2CF3)3 - .
[0112] The ionic liquid may also contain a lithium salt.
[0113] At least one selected from the positive electrode 201 , the electrolyte layer 202 , and the negative electrode 203 may contain a binder for the purpose of improving the adhesion between particles.
[0114] The example of the binder is polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamideimide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polyether sulfone, polyhexafluoropropylene, styrene-butadiene rubber or carboxymethyl cellulose. As the binder, copolymers can also be used. The example of the binder is a copolymer of two or more materials selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, chlorotrifluoroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid and hexadiene. A mixture of two or more selected from the above materials can also be used.
[0115] At least one selected from the positive electrode 201 and the negative electrode 203 may contain a conductive auxiliary agent for the purpose of improving electron conductivity.
[0116] Examples of conductive additives are:
[0117] (i) Graphites such as natural graphite or artificial graphite,
[0118] (ii) Carbon blacks such as acetylene black or Ketjen black,
[0119] (iii) Conductive fibers such as carbon fibers or metal fibers,
[0120] (iv) fluorinated carbon,
[0121] (v) Metal powders such as aluminum,
[0122] (vi) Conductive whiskers such as zinc oxide or potassium titanate,
[0123] (vii) conductive metal oxides such as titanium oxide, or
[0124] (viii) Conductive polymer compounds such as polyaniline, polypyrrole or polythiophene For cost reduction, the conductive auxiliary agent described in (i) or (ii) above may be used.
[0125] Examples of the shape of the battery of the second embodiment include a coin shape, a cylindrical shape, a square shape, a sheet shape, a button shape, a flat shape, and a laminated shape.
[0126] The battery of the second embodiment can also be manufactured, for example, by preparing a positive electrode forming material, an electrolyte layer forming material, and a negative electrode forming material, and fabricating a stacked body in which a positive electrode, an electrolyte layer, and a negative electrode are arranged in this order by a known method.
[0127] Example
[0128] Hereinafter, the present disclosure will be described in more detail using examples.
[0129] (Example 1)
[0130] [Production of solid electrolyte materials]
[0131] In a dry atmosphere with a dew point below -30°C (hereinafter referred to as "dry atmosphere"), Li2O2 and TaCl5 are prepared as raw powders in a manner to achieve a molar ratio of Li2O2:TaCl5=0.65:1.0. These raw powders are crushed and mixed in a mortar to obtain a mixed powder. The mixed powder is placed in a quartz glass filled with argon and fired at 320°C for 3 hours. The obtained fired product is crushed in an agate mortar. In this way, the solid electrolyte material of Example 1 is obtained. The molar ratio Li / M is 1.3. In addition, the molar ratio is a value obtained from the molar ratio of the raw powder. The same applies to the molar ratio Li / M in the following Examples 2 and 3 and Comparative Examples 1 and 2.
[0132] [Evaluation of ion conductivity]
[0133] Figure 3 A schematic diagram showing a press mold 300 for evaluating the ion conductivity of a solid electrolyte material.
[0134] The press forming die 300 includes a punch upper portion 301, a frame die 302, and a punch lower portion 303. The frame die 302 is formed of insulating polycarbonate. The punch upper portion 301 and the punch lower portion 303 are both formed of electronically conductive stainless steel.
[0135] use Figure 3 The press molding die 300 shown was used to measure the ion conductivity of the solid electrolyte material of Example 1 by the following method.
[0136] In a dry atmosphere, the powder of the solid electrolyte material of Example 1 (i.e. Figure 3 The solid electrolyte material powder 101 is filled in the press mold 300. In the press mold 300, a punch upper portion 301 is used to apply a pressure of 300 MPa to the solid electrolyte material of Example 1.
[0137] While keeping the pressure on the evaluation cell unchanged, the upper punch 301 and the lower punch 303 were connected to a potentiostat (VersaSTAT4 manufactured by Princeton Applied Research) equipped with a frequency response analyzer. The upper punch 301 was connected to the working electrode and the potential measurement terminal. The lower punch 303 was connected to the counter electrode and the reference electrode. The ionic conductivity of the solid electrolyte material of Example 1 was measured by electrochemical impedance spectroscopy at room temperature. As a result, the ionic conductivity measured at 22°C was 5.8 mS / cm.
[0138] [Evaluation of heat resistance]
[0139] In order to evaluate the heat resistance of the solid electrolyte material, the solid electrolyte material of Example 1 was heat treated at 200°C for 3 hours in an argon atmosphere. Then, the ionic conductivity of the solid electrolyte material of Example 1 was measured at room temperature. The method for measuring the ionic conductivity is the same as the method described in the above-mentioned [Evaluation of ionic conductivity]. As a result, the ionic conductivity measured at 22°C was 6.6mS / cm. In this way, the ionic conductivity of the solid electrolyte material was not reduced by heat treatment. In other words, the solid electrolyte material of Example 1 has excellent heat resistance.
[0140] [X-ray diffraction]
[0141] Figure 4 This is a graph showing the X-ray diffraction spectrum of the solid electrolyte material of Example 1. Figure 4 The results shown were determined by the following method.
[0142] The X-ray diffraction pattern of the solid electrolyte material of Example 1 was measured using an X-ray diffractometer (MiniFlex600 manufactured by RIGAKU) in a dry atmosphere with a dew point of -45°C or less. Cu-Kα rays (wavelength and ).
[0143] The solid electrolyte material of Example 1 had a first peak and a second peak at 13.54° and 14.88°, respectively. The intensity ratio of the first peak to the second peak (hereinafter referred to as "intensity ratio I1 / I2") was 1.05.
[0144] (Examples 2 and 3 and Comparative Examples 1 and 2)
[0145] [Production of solid electrolyte materials]
[0146] In Example 2, Li2O2 and TaCl5 were prepared as raw material powders in a molar ratio of Li2O2:TaCl5=0.7:1.0. The molar ratio Li / M was 1.4.
[0147] In Example 3, Li2O, LiOH and TaCl5 were prepared as raw material powders in a molar ratio of Li2O:LiOH:TaCl5=0.4:0.4:1.0. The molar ratio Li / M was 1.2.
[0148] Solid electrolyte materials of Examples 2 and 3 were obtained in the same manner as in Example 1 except for the above matters.
[0149] In Comparative Example 1, Li2O2 and TaCl5 were prepared as raw material powders in a dry atmosphere in a molar ratio of Li2O2:TaCl5=0.8:1.0. These raw material powders were crushed and mixed in a mortar to obtain a mixed powder. The mixed powder was placed in a quartz glass filled with argon and fired at 355°C for 3 hours. The obtained fired product was crushed in an agate mortar. In this way, the solid electrolyte material of Example 1 was obtained. The molar ratio Li / M was 1.6.
[0150] In Comparative Example 2, Li2O and TaCl5 were prepared as raw material powders in a molar ratio of Li2O:TaCl5=0.6:1.0. The molar ratio Li / M was 1.2. The solid electrolyte material of Comparative Example 2 was obtained in the same manner as Comparative Example 1 except for the above matters.
[0151] [Evaluation of ion conductivity]
[0152] The ion conductivity of the solid electrolyte materials of Examples 2 and 3 and Comparative Examples 1 and 2 was measured in the same manner as in Example 1. Table 1 shows the measurement results.
[0153] [Evaluation of heat resistance]
[0154] The ion conductivity after heat treatment was measured for the solid electrolyte materials of Examples 2 and 3 and Comparative Examples 1 and 2 in the same manner as in Example 1. Table 1 shows the measurement results.
[0155] [X-ray diffraction]
[0156] In the same manner as in Example 1, X-ray diffraction patterns of the solid electrolyte materials of Examples 2 and 3 and Comparative Examples 1 and 2 were measured. Figure 4 The measurement results are shown in .
[0157] The solid electrolyte material of Example 2 had the first peak and the second peak at 13.51° and 14.83°, respectively. The intensity ratio I1 / I2 was 0.70.
[0158] The solid electrolyte material of Example 3 has the first peak and the second peak at 13.54° and 14.85°, respectively. The intensity ratio I1 / I2 is 1.72.
[0159] The solid electrolyte material of Comparative Example 1 had the first peak and the second peak at 13.55° and 14.82°, respectively. The intensity ratio I1 / I2 was 0.41.
[0160] The solid electrolyte material of Comparative Example 2 had the first peak and the second peak at 13.58° and 14.92°, respectively. The intensity ratio I1 / I2 was 4.75.
[0161] Table 1
[0162]
[0163] (Inspection)
[0164] Table 1 shows that the solid electrolyte materials of Examples 1 to 3 have a high ion conductivity of 4.0 mS / cm or more at room temperature, and the ion conductivity does not decrease even after heat treatment at 200° C. for 3 hours.
[0165] Comparison between Examples 1 to 3 and Comparative Example 1 shows that by setting the value of the intensity ratio I1 / I2 to be 0.5 or more, a solid electrolyte material in which a decrease in ion conductivity is suppressed can be realized even when heat-treated at 200°C for 3 hours.
[0166] Comparison between Examples 1 to 3 and Comparative Examples 1 and 2 shows that by setting the value of the intensity ratio I1 / I2 to be 4.50 or less, a solid electrolyte material can be realized in which a decrease in ion conductivity is suppressed even after heat treatment.
[0167] Since the solid electrolyte materials of Examples 1 to 3 do not contain sulfur, hydrogen sulfide is not generated.
[0168] As described above, the solid electrolyte material of the present disclosure has practical ion conductivity and can reduce the decrease in ion conductivity caused by heat. Therefore, the solid electrolyte material of the present disclosure is suitable for providing a battery with excellent charge and discharge characteristics.
[0169] Industrial Applicability
[0170] The battery disclosed in the present invention can be used, for example, in an all-solid lithium-ion secondary battery.
Claims
1. A solid electrolyte material, which is a solid electrolyte material containing Li, M, O and X, wherein: M is at least one selected from Nb and Ta, X is at least one selected from F, Cl, Br and I, The solid electrolyte material has a first peak located within a range of a diffraction angle 2θ of 13.49° to 13.59° and a second peak located within a range of a diffraction angle 2θ of 14.82° to 14.92° in an X-ray diffraction pattern obtained by X-ray diffraction measurement using Cu-Kα rays, The intensity ratio of the first peak to the second peak is 0.50 or more and 4.50 or less, The molar ratio of Li to M is 1.2 or more and 1.4 or less.
2. The solid electrolyte material according to claim 1, wherein X contains Cl.
3. The solid electrolyte material according to claim 1 or 2, wherein M contains Ta.
4. The solid electrolyte material according to any one of claims 1 to 3, wherein The strength ratio is greater than or equal to 0.70 and less than or equal to 1.
72.
5. A battery, wherein: have: positive electrode, Negative electrode, and an electrolyte layer disposed between the positive electrode and the negative electrode; At least one selected from the positive electrode, the negative electrode, and the electrolyte layer contains the solid electrolyte material according to any one of claims 1 to 4.
Citation Information
Patent Citations
Solid electrolyte material and battery using same
WO2020137153A1
Solid electrolyte material and battery using same
WO2020137155A1
Blended cathode materials
CN103828099A
Electrolyte, battery, electronic apparatus, and methods for producing electrolyte and battery
CN111326800A
Cathode active material, cathode comprising the same and lithium battery using the cathode
KR1020110011497A
